Analysis on How Learning Motivation And The Understanding of Information Technology Affects Accounting Students Cumulative Grade Point Average (GPA) - Yolanda, Nabila; Izzati, Dina; Zahrani, Vista; Delani, Maisya; Fachruddin, Wan (Indonesian Journal Publisher, 2025)
This study examines the relationship between accounting students' cumulative grade point average (GPA) and their information technology proficiency and motivation to learn. In the current digital era, success in the accounting business, where managing and reporting financial data is essential, increasingly depends on having a strong information technology background. The study used a survey methodology and a quantitative approach, focusing on 50 accounting students in Medan. A standardized questionnaire measuring demographics, learning motivation, and IT comprehension was used to gather data. Information technology knowledge and GPA have a significant positive link (p = 0.001), according to the data, suggesting that improving students' IT proficiency can significantly raise their academic achievement. On the other hand, learning motivation's impact on GPA is not statistically significant (p = 0.096), indicating that although motivation is relevant, other elements might be more crucial for academic achievement. To improve overall academic performance in accounting education, the findings highlight the necessity for educational institutions to concentrate on enhancing students' IT comprehension in addition to learning motivation tactics.